1995
DOI: 10.1172/jci117962
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of very late antigen-4 integrin binding to fibronectin with connecting segment-1 peptide reduces accelerated coronary arteriopathy in rabbit cardiac allografts.

Abstract: Graft arteriopathy, a leading cause of cardiac allograft failure, is associated with increased intimal smooth muscle cells, inflammatory cells, and accumulation of extracellular matrix. We hypothesized that cellular fibronectin plays a pivotal role in the progression of the allograft arteriopathy by directing the transendothelial trafficking of inflammatory cells through interaction of the connecting segment-i (CS1) motif with the very late antigen-4 (VLA-4) integrin, and tested this in vivo using a blocking p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
1
3

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 46 publications
3
62
1
3
Order By: Relevance
“…The results imply that therapeutic interventions targeted at interactions between T cells and ECMP (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) will be only partially effective in collagenous tissues if they do not block the costimulatory effects of type I collagen. This possibility is supported by the reports that VLA-4-blocking peptide and mAb are unable to inhibit cutaneous contact hypersensitivity, delayed-type hypersensitivity, or adjuvant arthritis in rodents by more than 35-60% (14,15,20,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results imply that therapeutic interventions targeted at interactions between T cells and ECMP (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) will be only partially effective in collagenous tissues if they do not block the costimulatory effects of type I collagen. This possibility is supported by the reports that VLA-4-blocking peptide and mAb are unable to inhibit cutaneous contact hypersensitivity, delayed-type hypersensitivity, or adjuvant arthritis in rodents by more than 35-60% (14,15,20,25).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence that VLA-4 is a ligand for the alternatively spliced connecting segment 1 domain of fibronectin, and for VCAM-1, which both deliver costimulatory signals in T cells, has identified this integrin as a therapeutic target. This has led to multiple reports of the development and testing of potentially therapeutic VLA-4 Abs and peptide ligands, both in vitro and in animal models of inflammatory and autoimmune diseases, and transplantation (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Early human studies with VLA-4 targeting agents are also in progress, for example in patients with multiple sclerosis (26,27).…”
mentioning
confidence: 99%
“…In conclusion, the study reported by Molossi et al (1) in this issue of The Journal is highly significant and represents a careful and well-planned first step towards preventing atherogenic changes in grafted organs. Like any good piece of research, however, their studies raise fundamental biological questions to which we have, as yet, no answers.…”
Section: Editorialmentioning
confidence: 80%
“…It was with a great deal of trepidation that I agreed to comment on the report by Molossi et al (1) in this issue of The Journal. Not being trained as a physician or a cardiologist and never having seen a person with a transplanted heart, I was hesitant (even though the Editors told me that this was my chance "to be famous").…”
Section: Editorialmentioning
confidence: 84%
See 1 more Smart Citation